Prevalence of severe esophagitis in Spain. Results of the PRESS study (Prevalence and Risk factors for Esophagitis in Spain: A cross-sectional study). Issue 2 (April 2016) - Piqué, Núria; Ponce, Marta; Garrigues, Vicente; Rodrigo, Luis; Calvo, Félix; de Argila, Carlos Martín; Borda, Fernando; Naranjo, Antonio; Alcedo, Javier; José Soria, María; Rey, Enrique; Bujanda, Luis; et al.
Background: *N.P. and M.P. contributed equally to this study. The current prevalence of esophagitis in southern Europe is unknown. In addition, the risk factors for reflux esophagitis are not fully understood. Objective: The objective of this article is to assess the prevalence and risk factors for esophagitis in Spain. Methods: A prospective, observational, cross-sectional, multicenter study (PRESS study) was conducted among 31 gastrointestinal endoscopy units throughout Spain. A total of 1361 patients undergoing upper gastrointestinal endoscopy were enrolled. Sociodemographic, clinical and treatment data were recorded. Results: A total of 95% of patients were Caucasian and 52% were male (mean age: 53 ± 17 years). The most frequent symptoms prompting endoscopy were heartburn (40%), regurgitation (26%) and dysphagia (15%). Fifty-four percent of patients undergoing endoscopy were receiving proton pump inhibitor (PPI) treatment. Esophagitis (mainly mild-moderate) was present in 154 (12.4%) patients. The severe form was recorded in only 11 (0.8%) patients. Multivariate analysis results indicated that the likelihood of esophagitis was higher in men (OR = 1.91, 95% CI = 1.31–2.78), in patients with high GERD-Q scores (OR = 1.256, 95% CI = 1.176–1.343), weight increase (OR = 1.014, 95% CI = 1.003–1.025) and high alcohol consumption (OR = 2.49, 95% CI = 1.16–5.36). Conclusion: Severe esophagitis is a rare finding in the Spanish population. Male gender, high GERD-Q score, weight increase and high alcohol consumption are main risk factors for its appearance.